Clinical and Radiological Presentations of Various Pulmonary Infections in Hospitalized Diabetes Mellitus Patients: A Prospective, Hospital-Based, Comparative, Case Series Study. (20th March 2021) - Vishwakarma, Pravesh; Usman, Kauser; Garg, Rajiv; Bajpai, Jyoti; Sethi, Rishi; Pradhan, Akshyaya
Abstract : Background . Diabetes mellitus is associated with increased rate of respiratory tract infections. The objective was to compare demographic, clinical, serum biochemical, and typical and atypical radiological profiles among hospitalized diabetics and nondiabetics with lower respiratory tract infection. Material and Methods . A prospective, hospital-based, consecutive, comparative observational study of 12-month study duration was conducted. Patients aged 13–90 years diagnosed with lower respiratory tract infection with or without diagnosed diabetes mellitus participated in the study. Demographic, clinical, serum biochemistry, and radiological profiles of diabetics (n = 44 ) and nondiabetics (n = 53 ) were compared. Results . Diabetics were older than nondiabetics at presentation (p < 0.0001 ). Difference in mean random blood sugar (RBS) (p < 0.001 ), fasting blood sugar (FBS) (p < 0.001 ), and postprandial blood sugar (PPBS) (p < 0.0001 ) was significant between diabetics and nondiabetics. Nondiabetics more frequently presented with fever (p = 0.0032 ), chest pain (p = 0.0002 ), and hemoptysis (p = 0.01 ) as compared to diabetics. Diabetics more frequently presented with extreme temperatures (hypothermia or hyperpyrexia) (p = 0.022 ), lower serum sodium levels (p = 0.047 ), and lower partial arterial pressure (p < 0.001 ) than nondiabetics. The mean pneumonia patient outcomes research team (PORT) risk score was higher in diabetics (124.84 ± 41.31 ) compared to nondiabetics (77.85 ± 39.77 ) (p < 0.001 ). Diabetics more commonly displayed bilateral lesions with multilobe or lower lobe involvement, the most common type of lesion being exudative. Conclusion . Diabetic patients usually had severe pulmonary infection and poor prognosis as suggested by higher mean PORT risk score. They also more frequently presented with bilateral lesions with multilobe or lower lobe involvement as evidenced by radiography as compared to nondiabetic patients.